'Bushfalling': the ambiguities of role identities experienced by self-sponsored Cameroonian students in Flanders (Belgium). Issue 6 (2nd November 2019) - E. Wanki, Presca; Lietaert, Ine
ABSTRACT: Educational mobility in Cameroon is not a recent phenomenon, yet through the notion of 'bushfalling' – that is, the way international migration is envisioned and constructed in Cameroon – young Cameroonians explore routes to new destination countries for educational migration as a way of fulfilling their dreams of a better future. These dreams are enabled and challenged by the different role identities the students have to combine in the destination country. This article focuses on self-sponsored Anglophone Cameroonian students in Flanders, who combine roles as students, workers and transnational caregivers. Using bushfalling as our analytical lens, we explore the change in understanding bushfalling through the educational route and its implications for transnational family relations. Further, we explore the various ways in which these students negotiate and manipulate the different roles, yet keep the student role identity in the centre, and how this in turn informs their next step in the education-migration trajectory.